Analisis Kesesuaian Implementasi Pembiayaan Dana Talangan Haji di Perbankan Syari’ah dengan Fatwa Mui - Irfan Nurudin (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
Bailouts of Hajj aims to facilitate community who are less able to perform the pilgrimage. At the beginning of this financing is not a problem. But in its development began to emerge: first, the problem of how to regulate the imposition ujroh Islamic banks in financing. Second, how the impact of the financing, and third, what alternative solutions if financing bailouts Hajj is still problematic. Research methods in this study is the first empirical study, the types of legal research or sociology, and the approach used is a normative approach. Second, the source of the data required primary and secondary data is data by using the law. Third, how data collection using brochures and documents the official bailouts of the Hajj. Fourth, the method used is the method of deductive reasoning and qualitative analysis. The results of this research will address, first, the analysis based on the theory of the bailouts and the theory of the riba, then whether the implementation of financing bailouts of their Hajj there are still elements of usury. Second, if reviewed maslahah, then what is the impact of bailouts of Hajj? Third, try to find an alternative solution.